Permeation and trapping of hydrogen in Eurofer97. (December 2021) - Montupet-Leblond, F.; Corso, L.; Payet, M.; Delaporte-Mathurin, R.; Bernard, E.; Charles, Y.; Mougenot, J.; Vartanian, S.; Hodille, E.A.; Grisolia, C.
Abstract: Diffusion and trapping of hydrogen isotopes in fusion materials need to be fully described in order to evaluate permeation and retention in fusion reactors walls and breeding blankets. Hydrogen gas permeation experiments have been conducted on Eurofer97 with pressures ranging from 1 0 1 to 1 0 5 Pa and temperatures between 473 K and 673 K, resulting in solubility K (T) (mol m −3 Pa − 1 2 )=  1 . 76 ⋅ 1 0 − 1 exp ( − 0 . 27 ( eV ) k B T ), diffusivity D (T) (m 2  s −1 )  = 2 . 52 ⋅ 1 0 − 7 exp ( − 0 . 16 ( eV ) k B T ) and permeability Φ (T) (mol m −1 Pa − 1 2 s −1 )  = 4 . 43 ⋅ 1 0 − 8 exp ( − 0 . 43 ( eV ) k B T ) . Trapping parameters have been investigated using thermal desorption spectrometry of deuterium-loaded samples coupled with parametric optimization, leading to detrapping energies E dt, 1 = 0 . 51 eV, E dt, 2 = 1 . 27 eV, E dt, 3 = 1 . 65 eV and densities N t, 1 = 6 . 01 ⋅ 1 0 25  m −3, N t, 2 = 6 . 44 ⋅ 1 0 22  m −3, N t, 3 = 3 . 88 ⋅ 1 0 23  m −3 . This parametric optimization is performed using a kinetic surface model: the contribution of this model is compared to the results given by solubility and recombination rate models. Highlights: Gas permeation yields diffusivity, permeability and solubility of H in Eurofer97. Effective diffusivity gives the density and energy of the dominant trap. Thermal desorption spectrometry up to 873K shows three trapping sites. Using MHIMS, we get energies and densities of the three traps and surface energies.